Oral toxicity of small microplastic of polyamide assessed by a standardized guideline study - Roland Buesen; Stefanie Vogel; Tizia Thoma; Volker Strauss; Sibylle Gröters; Kathrin Becker; Frank Müller; Till Gründling; Patrizia Pfohl; Amelie Vogel; Andrea Haase; Wendel Wohlleben (Microplastics and Nanoplastics)
Abstract There is a dire lack of standardized in vivo studies investigating the human hazard by microplastics by OECD test guidelines. The lack of suitable test materials contributes to this situation. Here we report on results of test guideline 407 with 28-day oral exposure of male rats to small microplastic (polyamide (PA-6) with a size distribution from 2.2 µm to 16.5 µm). The tested material was chosen by the boundary conditions that a relatively large amount (0.3 kg) should be available with size as small as possible, with realistic shapes (irregular, not spherical) and with composition as representative as possible for pristine PA-6. The conditions were met by extracting the smallest 0.1% of particles from the “fines” that are rejected during commercial production of 3D printing powder, whereof tons are produced as intermediate for selective laser sintering. This strategy of generating larger amounts of microplastic test materials may be accessible also for other types of plastic. The study was performed as limit test in accordance with OECD test guideline 407 applying 1000 mg test substance/kg body weight/day for 28 days. Hematological and clinical chemical examinations were performed at the end of the administration period. All organs listed in the guideline were assessed, including histopathology. Under the current study conditions, no local or systemic toxicological effects were seen after 28-day oral exposure to PA-6.